Antimicrobial Activities of Six Types of Honey towards Selected Pathogenic Microorganisms - Rhumaa, Abdurrahman; Rizekb, Amira; Elmegrahib, Najat; Eletrib, Ateia (مجلة العلوم الإنسانية والتطبيقية, 2017)
The emergence of strains of pathogenic microorganisms with resistance to commonly used antibiotics has necessitated a search for novel types of antimicrobial agents. It is of a great importance to understand the efficiency of honey against microorganisms. The main objective of this study was to investigate the biological activities of Black Seed (Nigella sativa) honey, Thymus honey, Myrrh honey, Tamarix honey, Spring honey and Zizphus honey before and after exorcism against four pathogenic bacteria and one pathogenic fungi. Agar diffusion, Minimum Inhibitory Concentration and Minimum Killing Concentration methods were used to evaluate the antimicrobial activity. All the Gram-positive and Gram-negative bacteria tested were found to be inhibited to some extent by the six different honeys, although the antimicrobial potency was highly dependent upon type of honey and test organism. The honey samples were especially active against methicillin-resistance Staphylococcus aureus (isolated from Tripoli Medical Center), S. aureus ATCC 43300), Pseudomonas. aeruginosa ATCC 27893, . Escherichia coli ATCC 35150 and the yeast Candida albicans that isolated from Al-jala hospital. S. aureus was found to be particularly sensitive to Thymus exorcism honey. However, C. albicans found to be sensitive to Spring honey. In addition, the results showed that Tamarix exorcism honey was significantly (P = 0.006) more active than the Tamarix honey, also N. sativa exorcism honey was significantly (P = 0.003) more active than the N. sativa honey. The Minimum Inhibitory Concentration (MIC) of Tamarix exorcism honey (determined by tube dilution) for MRSA is more effective than 32-fold lower at 3.125% (V/V) compared to the other five honeys. The Minimum killing concentration was 6.25% concentration against S. aureus. The honey samples studied proved to be a good source of antimicrobial agents that might serve to fight against several diseases. These data also demonstrate that antimicrobial potency of honeys is highly dependent upon both the target microbial species and the type of honey.